The Role of Hysteroscopic Surgery in Treating Uterine Abnormalities and Its Impact on Pregnancy Outcomes. A clinical study - Arifa Inayat, Rehana Kamal, Firdous Ara, Shabana Bano Soomro, Afshan Mushtaq, Shameem Bhatti (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Uterine abnormalities, including congenital malformations, intrauterine adhesions, submucosal fibroids, endometrial polyps, and chronic endometritis are associated with infertility, recurrent pregnancy loss, and obstetric complications. Hysteroscopic surgery offers a minimally invasive alternative to traditional open surgical approaches associated with higher morbidity. Methodology: A prospective clinical study was done at Gynecology unit -3 Civil Hospital Quetta, Pakistan from March 2022 to January 2023. Two hundred women in the age group of 20–45 years with documented uterine abnormalities by ultrasound, hysterosalpingography, or diagnostic hysteroscopy were enrolled. Demographic and clinical data including age, BMI, duration of infertility, and reproductive history were recorded in detail. The 5 mm operative hysteroscope with a 30° lens was used for hysteroscopic procedures such as septum resection, adhesiolysis, myomectomy, and polypectomy. The pregnancy rates, time to conception, miscarriage and live birth rates, and postoperative complications were assessed in patients followed for 12 months. SPSS was used for statistical analysis and logistic regression was conducted to identify the predictors of successful outcomes. Results: Mean time to conception was 4.5 months and overall pregnancy rate was 70%. The miscarriage rate was 14.3% and the live birth rate was 78.6% among pregnancies. The postoperative complication rate was 5%. Age also decreased the odds of a positive outcome (OR=0.92, p=0.002) in the logistic regression. Conclusion: Hysteroscopic surgery is a safe and effective intervention for uterine abnormalities, improving reproductive outcomes. Given the negative effect of advancing age, early intervention is recommended. Keywords: Hysteroscopic surgery, uterine abnormalities, infertility, pregnancy outcomes, minimally invasive. Further studies will expand these findings.